Anatomical Step-by-Step Dissection of Complex Skull Base Approaches for Trainees: Surgical Anatomy of the Translabyrinthine and Transcochlear Approaches - Perry, Avital; Carlstrom, Lucas P.; Alexander, Alex Yohan; Leonel, Luciano C.P.C.; Nassiri, Ashley M.; Nguyen, Bachtri; Morris, Jonathan M.; Driscoll, Colin L.W.; Link, Michael J.; Graffeo, Christopher S.; Peris-Celda, Maria (Journal of Neurological Surgery Part B: Skull Base, 2024)
Introduction Skull base neuroanatomy is traditionally learned through two-dimensional anatomical atlases, which while are of unquestionable value, lack the nuanced association of three-dimensional relationships between fundamental anatomical structures relevant to surgical approaches. Surgically focused step-by-step anatomical dissections can augment trainee learning of complex skull base techniques, particularly multistep and nuanced techniques such as translabyrinthine and transcochlear approaches.Methods Translabyrinthine and transcochlear approaches were performed on six sides of three formalin-fixed latex-injected specimens. The study objective was the completion and photo documentation of the steps involved in the approach in order to provide a comprehensive, intelligible, and anatomically oriented resource for multilevel trainees. Illustrative case examples were prepared to supplement approach dissections.Results The translabyrinthine and transcochlear approaches offer unique lateral windows through the temporal bone into the posterior fossa, providing excellent access to pathology at the petrous apex, internal auditory canal, Meckel's cave, and anterolateral brainstem. The transcochlear approach, which is an anterior extension of the translabyrinthine, particularly provides excellent exposure of the prepontine region and clivus. Important surgical considerations include patient position, temporal bone drilling and identification of critical landmarks, dural opening and identification of neurovascular structures, and reconstruction/closure techniques.Conclusion The translabyrinthine and transcochlear approaches are fundamental techniques for lateral skull base and posterior fossa pathologies. Both approaches are hearing-sacrificing but often require minimal to no cerebellar retraction and deliver unique visualization of prepontine neurovascular structures. This step-by-step approach guide provides a unique practical and high-yield surgically oriented learning resource for neurosurgery and otolaryngology trainees.
Keywords: complex cranial surgery; cerebellopontine angle; education; lateral skull base; simulation; step-by-step; transcochlear; translabyrinthine